Weight optimization of hydrogen storage vessels for quadcopter UAV using genetic algorithm - Lee, Youngheon; Park, Eu-Tteum; Jeong, Jinseok; Shi, Hayoung; Kim, Jeong; Kang, Beom-Soo; Song, Woojin (International journal of hydrogen energy, 2020)
Multicopter is relatively easy to control and is used in various fields. Typical multicopter drones use batteries as a power source, but it has limitations in flight time. The aim of this study is to contribute to the increase of flight time through the use of hydrogen fuel cells and weight reduction of drones. In this study, the weight of hydrogen storage vessel is optimized using a genetic algorithm and a numerical analysis based on the Tsai-Wu failure theory. As a result, the vessel weight was reduced by more than 23.79% compared to the initial weight in the algorithm iteration. To confirm that the weight optimization and using hydrogen fuel cell improved flight time, the hovering times are calculated. Consequently, the hovering time when using the hydrogen fuel cell is increased by 37.85% than using the batteries. And the hovering time increased by 17.73% with optimized vessel weight. •The weights of hydrogen storage vessels are optimized using genetic algorithms.•The hydrogen storage vessels analyze with Tsai-Wu failure theory.•Hovering times of UAVs applied the optimized vessels are predicted and compared.